2018
DOI: 10.1113/ep086760
|View full text |Cite
|
Sign up to set email alerts
|

A vascular mechanism to explain thermally mediated variations in deep‐body cooling rates during the immersion of profoundly hyperthermic individuals

Abstract: Physiologically trivial time differences for cooling the intrathoracic viscera of hyperthermic individuals have been reported between cold- and temperate-water immersion treatments. One explanation for that observation is reduced convective heat delivery to the skin during cold immersion, and this study was designed to test both the validity of that observation, and its underlying hypothesis. Eight healthy men participated in four head-out water immersions: two when normothermic, and two after exercise-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Indeed, a recent study found similar cooling rates using 14°C and 26°C water due to an attenuated vasoconstrictor drive at 26°C (161). Nevertheless, the mixture of warm 'central blood' with cool 'peripheral blood', will reduce core body temperature after termination of immersion in very cold water (i.e.…”
Section: External Cooling and Thermal Responsesmentioning
confidence: 99%
“…Indeed, a recent study found similar cooling rates using 14°C and 26°C water due to an attenuated vasoconstrictor drive at 26°C (161). Nevertheless, the mixture of warm 'central blood' with cool 'peripheral blood', will reduce core body temperature after termination of immersion in very cold water (i.e.…”
Section: External Cooling and Thermal Responsesmentioning
confidence: 99%
“…Cold-water immersion of the torso compared with temperate-water immersion of the torso (20 CÀ 26 C/68 FÀ 78.8 F) 21,22,26 Cold-water immersion (14 C/57.2 F) of the torso compared with the use of colder-water immersion (8 C/46.4 F) 26 Cold-water immersion (14 C/57.2 F) of the torso compared with ice-water immersion (2 CÀ 5 C/35.6 FÀ 41 F) of the torso 14,26 Colder-water immersion (9 C/48.2 F) up to the iliac crest compared with passive cooling 50 Colder-water immersion (10 CÀ 12 C/50.0 FÀ 52.6 F) of the hands/feet compared with the use of colder-water immersion of the torso 29 Evaporative cooling compared with passive cooling 34,52 Evaporative cooling compared with use of ice packs applied to the neck, axilla, and groin 34,36 Evaporative cooling compared with the use of commercial ice packs applied to the whole body 34 Evaporative cooling combined with the use of commercial ice packs to the neck, axilla, and groin compared with passive cooling34 and evaporative cooling alone 34 Evaporative cooling compared with the administration of intravenous 0.9% normal saline at 20 C/68.0 F 36 Ice-sheet application (bed sheets soaked in ice water kept at 3 C/37.4 F and towels soaked in ice water kept at 14 C/57.2 F, respectively, to the body compared with passive cooling 24,38 Ice-sheet application (sheets soaked in ice and water at 5 CÀ 10 C; 33.8 FÀ 41.0 F) to the body compared with colder-water immersion (5 CÀ 10 C; 33.8 F À 41.0 F) 33 Commercial ice packs to the neck, groin, and axilla compared with passive cooling 34,35 Commercial ice packs to the whole body compared with passive cooling 34 Fanning alone compared with passive cooling 24,39 Hand-cooling devices compared with passive cooling 46,49,53 A commercial cooling jacket compared with passive cooling 44,46 Various cooling vests compared with passive cooling 24,39,44,…”
Section: Table 3 -Cooling Techniques With Comparisons Not Showing a Significant Mean Difference In Cooling Ratementioning
confidence: 99%
“…13,14) Subsequent research has not only replicated the thermal phase delays observed via the rectum during the whole-body cooling of hyperthermic individuals, but has also established a cutaneous vascular mechanism to explain those time-dependent observations. 19) Furthermore, that research group unequivocally demonstrated that the cutaneous vascular responses that accompany external cooling are powerfully influenced by the thermal state of the deep-body tissues prior to the initiation of external cooling. 4,20,21) Therefore, during hyperthermia, mild external cooling stimuli were found not to elicit the powerful vasoconstriction that was observed when similar stimuli were applied during normothermia.…”
Section: Introductionmentioning
confidence: 99%